NYADRAN TRADITION AND THE DYNAMICS OF RELIGIOUS MODERATION IN URBAN MUSLIM COMMUNITIES: AN ETHNOGRAPHIC STUDY IN NGAYUNG, EAST JAVA - Syarifah, Umaiyatus; Imamuddin, M. Imamuddin; Anita, Anita Andrini Ningsih; Fahimah, Siti Fahimah; Azka, Azka Gadallah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
Strengthening religious moderation in Indonesia is urgent nowadays due to the increasing level of global polarization and religious sectarianism. Here, the university and pesantren’s roles are crucial. However, local tradition containing similar values has not received proper attention, both from policymakers and academia. Therefore, this article explores the nyadran tradition in Ngayung Village, Lamongan, East Java as an example of Islamic moderation based on Javanese wisdom. This article addresses how nyadran serves as a mediator to maintain interreligious harmony in an Islamic moderation perspective carried out through tawasuth, tasamuh, i'tidal, al-Iṣlāḥ, al-qudwah, and muwāṭanah. This study utilized a qualitative ethnographic approach. During the six-month data collection, researchers employed participant observation, in-depth interviews with 18 informants, including religious leaders, village elders and youth, and document analysis. The findings indicate that nyadran offers a microcosmic example of Islamic dialogical life because of its inclusive nature of people from various social backgrounds and religious persuasions. Besides holding on to tradition, the community also creatively reinterprets nyadran as tathawwur wa ibtikār amidst the burgeoning influence of urban religiosity and digital religious narratives. Analytically, nyadran functions as a hybrid social mechanism bridging rural piety and urban religious awareness, resulting in a culturally rooted form of religious moderation. This study contributes to strengthening religious moderation discourse by demonstrating local traditions as a sustainable framework for maintaining harmony in an increasingly diverse and modern Indonesian Muslim society.